Liquid-Liquid Extraction and Spectrophotometric Determination of Cromium (VI) with o-Hydroxythiophenols In The Presence of Hydrophobic Amines - Verdizadeh, Naila A; Zalov, Ali Z; Abaskuliyeva, Ulviyya B; Ephendiyeva, Naiba N; Hasanova, Novrasta C (IJRDO-Journal of Applied Science, 2017)
The mixed-ligand complexes of chromium (VI) with o-hydroxythiophenols (HTPD) and itsderivatives [2-hydroxy-5-chlorothiophenol (HCTP), 2-hydroxy-5-bromothiophenol (HBTP), and 2-hydroxy-5-iodothiophenol (HITP)] in the presence of hydrophobic amines have been investigated byspectrophotometric method. The condition of complexing and extraction, physical-chemical andanalytical characteristics of this complex have been found. As hydrophobic amins aniline (An), Nmetilaniline(mAn) and N, N-dimetilaniline (dAn) were used. It has been found that mixed-ligandcomplex were formed in weakly acidic medium (pH 3.0 – 5.0). The optimal concentration of ohydroxythiophenols(HTPD) and Am for formation of the complex was found to be 1.0∙10-3 M and1.12∙10-3M, respectively. Maksimum of light absorption observed at 475-488 nm. The calculatedmolar absorptivities (emax) belong to the interval (2.7 – 3.02)× 104dm3 ·mol–1· cm–1 . Thestoichiometric coefficients of the reaction were determined by the Asmus method, by the relativeyield method and by the equilibrium shift method. The results show a complex composition of 1:3:3(Cr(III):HTPD:Am).A linear calibration graph drawn between absorbance and the metal ion concentrationindicates that Cr(III) may be determined in the range 0.5-16 μg ml-1. The extraction-photometricmethods of chromium determination have been worked out. The proposed method was appliedsuccessfully to determine amount of chromium in alloys and in soil.